HISTORICITY OF PADMAVAT: पद्मावत की ऐतिहासिकता - Kumar, Manish (International Journal of Research -GRANTHAALAYAH, 2018)
In Hindi literature, ’Padmavat’ is Daidipyaman Nakshatra. Jayasi created this epic in the 16th century in the typical Awadhi language. The sweetness, emotional beauty, Sufi spirituality and historicity of its language is not seen. The poet has created this epic with the sum of folk, imagination and history. Jayasi has created the ’Padmavat’ by combining the legend of Jauhar of Padmini, the queen of Choudaur, in the legend of the popular queen and Sugge of Awadh province. This epic is a mirror of medieval India. It shows the social, cultural, political and historical splendor of erstwhile Indian society. Various scholars of Hindi literature have examined the historicity of ’Padmavat’ in their own way. It is possible to test its historicity with important historical sources such as archaeological remains, inscriptions, contemporary literary texts and history books. Before examining the historicity of this work, it is mandatory to get information about the history of its creator. हिन्दी साहित्याकाश में ‘पद्मावत’ दैदिप्यमान् नक्षत्र है। जायसी ने 16 वीं सदी में ठेठ अवधी भाषा में इस महाकाव्य का सृजन किया था। इसकी भाषा की मिठास, भाव सौंदर्य, सूफी अध्यात्म और ऐतिहासिकता देखते नहीं बन पड़ती है। कवि ने इस महाकाव्य का सृजन लोक, कल्पना और इतिहास के योग से की है। जायसी ने अवध प्रांत की लोकप्रचलित रानी और सुग्गे की कथा में चिŸाौड़ की रानी पद्मिनी के जौहर की कथा का सम्मिश्रण कर, ‘पद्मावत’ का सृजन किया है। यह महाकाव्य मध्यकालीन भारतवर्ष का दर्पण है। इसमें तत्कालीन भारतीय समाज की सामाजिक, सांस्कृतिक, राजनीतिक और ऐतिहासिक वैभव दिखाई देता है। हिन्दी साहित्य के विभिन्न विद्वानों ने ‘पद्मावत’ की ऐतिहासिकता की परीक्षा अपने-अपने ढंग से की है। महत्वपूर्ण ऐतिहासिक स्त्रोत जैसे- पुरातात्विक अवशेष, शिलालेख, समकालीन साहित्यक ग्रंथ एवं इतिहास की पुस्तकों से इसकी ऐतिहासिकता की परीक्षा संभव है। इस रचना की ऐतिहासिकता की परीक्षा से पूर्व इसके रचनाकार के इतिहास के विषय में जानकारी प्राप्त करना अनिवार्य है।